THE CORRELATION BETWEEN ULTIMATE STRAIN ROLLED STEEL IN DRAWING WITH THE PARAMETERS OF MICROSTRUCTURE - E. V. Parusov; S. I. Gubenko; V. A. Lutsenko; A. B. Sychkov; A. V. Vedeneev (Литьë и металлургия, 2016)
The correlation of mechanical hardening to the degree of dispersion of the perlite (interlamellar spacings) and strength indices of rolled steel diameter of 6.5 mm made of steel grade C72D is showed. Using the method of hydrostatic weighing and X-ray analysis it was established that to increase the degree of the deformability of high-carbon rolled during hardware production is the most preferred way is high-temperature unscramble of rolled coils with following process of controlled accelerated air cooling. The results of the research could serve as a basis for the creation of an additional process of assessing the quality of cold wire by non-destructive testing.